2011
DOI: 10.1002/pssb.201147157
|View full text |Cite
|
Sign up to set email alerts
|

The role of interfaces in organic spin valves revealed through spectroscopic and transport measurements

Abstract: Interfaces between dissimilar materials are critical to the performance of many electronic devices. In electrical devices where the active transport is through an organic semiconductor (OSC) layer there are metallic electrodes to supply and remove the charge carriers. At metal/molecule and molecule/metal interfaces the electrical contact is usually not Ohmic. As a result, in most metal-organic semiconductors-metal devices charge injection is mainly governed by tunneling across the barriers. When the metal elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 67 publications
1
17
0
Order By: Relevance
“…Transport of SP carriers from the first FM electrode to the second depends upon the coupling between the FM and OSC at the interface (that affects spinterface) and the spacer properties such as spin scattering sources including HFI and SOC and carrier mobility which is affected by disorder, impurities, temperature etc . of the materials . In general, the spin polarization of the transport electrons in the OSCs is attenuated exponentially as e –d/λ S when electrons diffuse across the organic spacer with the thickness, d .…”
Section: Fundamental Conceptsmentioning
confidence: 99%
See 1 more Smart Citation
“…Transport of SP carriers from the first FM electrode to the second depends upon the coupling between the FM and OSC at the interface (that affects spinterface) and the spacer properties such as spin scattering sources including HFI and SOC and carrier mobility which is affected by disorder, impurities, temperature etc . of the materials . In general, the spin polarization of the transport electrons in the OSCs is attenuated exponentially as e –d/λ S when electrons diffuse across the organic spacer with the thickness, d .…”
Section: Fundamental Conceptsmentioning
confidence: 99%
“…In addition to spin valve effect, a different type of MR effect in OLEDs, the so‐called organic magnetoresistance (OMAR) has also been observed in a range of OSCs . Excellent reviews on different aspects of the organic spintronic devices can be found in the literature …”
Section: Introductionmentioning
confidence: 99%
“…These samples have allowed us to study the inorganic materials excluding possible contributions arising from the molecular layer, such as changes of the vacuum level of the OS. [ 6,14 ] Two different structures, related to those with BPhen studied above, were produced. Sample (C) is composed of Co (8) (10), with the LiF layer above the ferromagnetic electrode.…”
Section: Communicationmentioning
confidence: 99%
“…The complex nature of organic/inorganic ferromagnetic interfaces has been emphasized in recent publications. 4,5,[9][10][11] In particular, the specific chemical bonding between the adsorbed organic molecule and the ferromagnetic surface is expected to dramatically influence the polarization of the injected electrons. For instance, the spin polarization at the Co=Alq 3 and ðLa; SrÞMnO 3 =Alq 3 interfaces has been found positive in Ref.…”
Section: Introductionmentioning
confidence: 99%